Kepuasaan Pasien pada Puskesmas Way Halim Bandar Lampung - Dory Efriyady (Journal of Management and Creative Business, 2023)
Which is comprehensive in nature and its activities consist of promotive, preventive, curative and rehabilitative efforts. The cost factor for cheaper check-ups and medicines, as well as the easy-to-reach locations in each sub-district or sub-district are the main reasons why people choose the Puskesmas as a place for treatment. One of the Puskesmas in Bandar Lampung City is the Way Halim Health Center. Way Halim Health Center provides disease prevention services, consultations, and treatment advice to patients. The Way Halim Health Center also provides outpatient treatment accompanied by additional inpatient facilities according to the patient's medical indications. The purpose of this research is to find out whether the quality of health services and facilities has an influence on patient satisfaction at the Way Halim Health Center in Bandar Lampung. The type of research used in this research is quantitative research. The population used was Way Halim Health Center in Bandar Lampung. The sampling technique used in this study was non-probability sampling with purposive sampling using the slovin formula so that the sample used was 97 respondents, namely Way Halim Health Center patients in Bandar Lampung. Collecting data using literature, documentation, observation, interviews and questionnaires. The data analysis tool uses multiple linear regression tests, correlation coefficient tests, t tests, f tests and R2 tests. Based on the results of the study, it showed that the quality of services and health facilities had a significant and significant effect on patient satisfaction who carried out health checks at the Way Halim Health Center in Bandar Lampung. The influence of the quality of health services and facilities has an effect of 69.9% on patient satisfaction who conducts health checks at the Way Halim Health Center in Bandar Lampung. While the remaining 30.1% is influenced by other factors not examined in this study.